World in flames - Jackson, Alex.; Ceppara, Renato ([s.l] : Lamancha Prodiction Ltd., 1984)
From Hitler's rise to power to the catastrophic bombing of Hiroshima, this film series chronicles the major events, battles and strategic moves of the various countries involved in Worl War II.
part 1. From Hitler's rise to power to the Blitzkrieg - part 2. From the Battle of Britain to Stalingrad - part 3. The war on the seas and the fall of Japan.
Copy available in DVD format.
Keywords: World War, 1939-1945.